2011
DOI: 10.1007/s10067-011-1829-8
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment bias in chronic pain research: whiplash as a model

Abstract: In science findings which cannot be extrapolated to other settings are of little value. Recruitment methods vary widely across chronic whiplash studies, but it remains unclear whether this generates recruitment bias. The present study aimed to examine whether the recruitment method accounts for differences in health status, social support, and personality traits in patients with chronic whiplash-associated disorders (WAD). Two different recruitment methods were compared: recruiting patients through a local whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
17
1
Order By: Relevance
“…Buitenhuis et al showed a high rate of sick leave among insurance claimants [16]. Differing recruitment methods likely explain the differences, and our lower figures [29]. Borchgrevink et al, in an ED-based study, found that 27% of 426 patients had been on sick leave, while Karlsborg et al reported a median absence from work of six days (0 days-9 months) [30,31].…”
Section: Discussioncontrasting
confidence: 44%
“…Buitenhuis et al showed a high rate of sick leave among insurance claimants [16]. Differing recruitment methods likely explain the differences, and our lower figures [29]. Borchgrevink et al, in an ED-based study, found that 27% of 426 patients had been on sick leave, while Karlsborg et al reported a median absence from work of six days (0 days-9 months) [30,31].…”
Section: Discussioncontrasting
confidence: 44%
“…The data obtained from these subjects have been analyzed previously with respect to determinants of long‐term functioning following whiplash injury as well as to recruitment bias in chronic pain research, but not with respect to possible sex differences, which is the focus of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Chronicity was defined as complaints persisting for at least 3 mo. A variety of recruitment procedures were used in order to prevent recruitment bias [26]. The inclusion criteria for the acute and chronic WAD group were experiencing symptoms resulting from a whiplash trauma and fulfilling the diagnostic criteria of WAD grade I to III as defined by the Quebec Task Force classification [1].…”
Section: Participantsmentioning
confidence: 99%